GANGGUAN KELEKATAN SEBAGAI PENCETUS TERJADINYA SKIZOFRENIA : TINJAUAN PUSTAKA - SITANGGANG, AMITA ROULI PURNAMA; ARDANI, I GUSTI AYU INDAH; LESMANA, COKORDA BAGUS JAYA (HEALTHY : Jurnal Inovasi Riset Ilmu Kesehatan, 2024)
Schizophrenia is one of the non-fatal diseases that result in a heavy burden for patients, society, and the government, with a prevalence rate of 0.5-1% of the world's population, or more than 20 million people worldwide. In Indonesia, according to the Ministry of Health of the Republic of Indonesia in 2019, it is estimated that there are 450,000 people with mental disorders, including schizophrenia. Although the exact cause of schizophrenia is not yet known, several factors are suspected to influence the occurrence of schizophrenia, one of which is emotional trauma due to attachment disorders. Attachment theory offers a conceptualization of the formation of emotional bonds, social functions, and emotional regulation that can help explain the occurrence of mental disorders, including schizophrenia. A literature review was conducted through data sources such as PubMed, Google Scholar, Medline, and PsycINFO to search for data on attachment theory, attachment disorders, and schizophrenia. Attachment disorders are experienced in the early stages of development in the form of trauma. Trauma experienced in the early stages of development, such as negative events, neglect, or inadequate caregiving, is a factor that can affect brain development, leading to changes in neuroendocrine function, resulting in disturbances in emotional regulation and cognitive function. There is a decrease in the ability to identify and understand one's own and others' mental states, such as beliefs, emotions, and intentions, known as "mentalization" and "theory of mind." Emerging evidence regarding the role of attachment in the development of psychosis has implications for the prevention and treatment of psychosis. Trauma experienced in the early stages of development, such as negative events, neglect, or inadequate caregiving, is considered a factor that can affect brain development and neuroendocrine function. The discussion on the relationship between attachment disorders and schizophrenia still requires extensive review and research in the future. ABSTRAKSkizofrenia termasuk salah satu kelompok penyakit nonfatal yang mengakibatkan beban berat bagi penderita, masyarakat, dan pemerintah dengan kisaran prevalensi antara 0,5-1 % dari populasi dunia, atau lebih dari 20 juta orang di seluruh dunia. Di Indonesia, menurut Kementerian Kesehatan RI tahun 2019 diperkirakan ada 450.000 orang dengan gangguan jiwa (ODGJ) termasuk skizofrenia. Meskipun penyebab skizofrenia belum diketahui secara pasti, terdapat beberapa faktor yang diduga mempengaruhi terjadinya skizofrenia, salah satunya adalah trauma emosional akibat gangguan kelekatan. Teori kelekatan menawarkan konseptualisasi tentang pembentukan ikatan emosional, fungsi sosial, dan regulasi emosi yang dapat membantu menjelaskan terjadinya gangguan mental termasuk skizofrenia. Dilakukan tinjauan pustaka melalui sumber data yaitu PubMed, Google Scholar, Medline, dan PsycINFO untuk mencari data mengenai teori kelekatan, gangguan kelekatan dan skizofrenia. Gangguan kelekatan dialami pada tahap awal perkembangan dalam bentuk trauma. Trauma yang dialami pada tahap awal perkembangan, misalnya peristiwa negatif, pengabaian atau pengasuhan yang tidak memadai merupakan faktor yang dapat mempengaruhi perkembangan otak, sehingga terjadi perubahan fungsi neuroendokrin sehingga terjadi gangguan regulasi emosi dan fungsi kognitif. Terdapat penurunan kemampuan untuk mengidentifikasi dan memahami kondisi mental diri sendiri dan orang lain, seperti keyakinan, emosi, dan niat, yang disebut sebagai “mentalisasi” dan “teori pikiran”. Bukti yang muncul mengenai peran keterikatan terhadap perkembangan psikosis mempunyai implikasi terhadap pencegahan dan pengobatan psikosis. Trauma yang dialami pada tahap awal perkembangan, misalnya peristiwa negatif, pengabaian atau pengasuhan yang tidak memadai dianggap sebagai faktor yang dapat mempengaruhi perkembangan otak serta fungsi neuroendokrin. Diskusi mengenai hubungan gangguan kelekatan dan skizofrenia masih memerlukan banyak telaah dan penelitian di masa depan.